2020
DOI: 10.1029/2019jc015220
|View full text |Cite
|
Sign up to set email alerts
|

A Turbulence‐Resolving Numerical Investigation of Wave‐Supported Gravity Flows

Abstract: Wave‐supported gravity flows (WSGFs) have been identified as a key process driving the offshore delivery of fine sediment across continental shelves. However, our understanding on the various factors controlling the maximum sediment load and the resulting gravity current speed remains incomplete. We adopt a new turbulence‐resolving numerical model for fine sediment transport to investigate the formation, evolution, and termination of WSGFs. We consider the simplest scenario in which fine sediments are supporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 49 publications
6
24
0
Order By: Relevance
“…Similar conclusions were drawn in Yue et al. (2020) for shore‐normal waves, and Cd was observed to be as low as Cd=0.002 when waves are shore‐parallel. The only DNS study on ACSTCs was conducted by Ozdemir and Yu (2018), which investigated the fluid dynamical details of the bi‐directional nature of ACSTCs, particularly focusing on the normal and shear Reynolds stress balance equations.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Similar conclusions were drawn in Yue et al. (2020) for shore‐normal waves, and Cd was observed to be as low as Cd=0.002 when waves are shore‐parallel. The only DNS study on ACSTCs was conducted by Ozdemir and Yu (2018), which investigated the fluid dynamical details of the bi‐directional nature of ACSTCs, particularly focusing on the normal and shear Reynolds stress balance equations.…”
Section: Introductionsupporting
confidence: 88%
“…when waves are normal to the shore. Similar conclusions were drawn in Yue et al (2020) for shore-normal waves, and d C was observed to be as low as  0.002…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations